Oral Red Pomegranate (Punica granatum) Extract Administration to Elevate Blood Glutathione Peroxidase Levels in Female Wistar Rats (Rattus Norvegicus) Following Maximum Physical Activity - Liena, Liena; Rahma Sari; Fioni, Fioni (Jurnal EduHealth, 2023)
There is a significant danger to human health from oxidative stress. This disorder does not have any apparent symptoms. However, it is linked to the start and progression of many diseases. There are also no established medical procedures for detecting oxidative stress. Finding out how oral administration of red pomegranate (Punica granatum) extract increases blood glutathione peroxidase levels in female rats (Rattus norvegicus) strains is the goal of this experimental quantitative study, which employs a pre-test-post-test control group design. Maximum physical activity was induced in Wistar rats. Twenty-four animals were used in the experiments, with six in each group. Three, four, and five milliliters of red pomegranate extract were used in this experiment. With an antioxidant value of 8.33 ppm, pomegranate extract (Punica granatum) was determined to have a very robust action, according to the research. In terms of composition, the 5-milliliter dose of red pomegranate (Punica granatum) extract outperforms the others when compared to average levels of glutathione peroxidase. Researchers discovered that supplementing with red pomegranate extract (Punica granatum) considerably raised glutathione peroxidase levels, suggesting that this fruit may aid in the body's antioxidant defenses against free radicals generated by strenuous exercise.